PENGENALAN OPERASIONAL BANK SYARIAH MELALUI LABORATORIUM RIIL BANKING - Idah Zuhroh (Trunojoyo University of Madura, 2012)
The practice of sharia banking in Indonesia has reached the age of twenty years. The rapid growth of sharia banks, has not as to as expected. Recently (in 2012), the market share of sharia banks still reached 3.8%. One obstacle to realize sharia banks as national banking trendsetter is still lack of public knowledge about the operations of sharia banks. In addition, the paradigm of sharia banks are more complex than conventional banks. Islamic bank managers mush have knowledge and entrepreneurial spirit. This paper aims to illustrate how efforts to introduce sharia banking operations can be performed in real terms in Sharia Banking Laboratory of the Faculty of Economics and Business (FEB) University of Muhammadiyah of Malang (UMM). A variety of treatment and observation can be done so as to strengthen the academic understanding of interest-free banks or banks with profit-sharing system. Some problems appear related to the operation of the bank towards the ideal lab, able to represent objective fact sharia bank development issues in Indonesia.